Additive manufacturing of bioresorbable poly(ester‐urethane)/glass‐ceramic composite scaffolds. Issue 8 (6th July 2022) - Lores, Nayla J.; Hung, Xavier; Talou, Mariano H.; Ballarre, Josefina; Abraham, Gustavo A.; Caracciolo, Pablo C.
Abstract: The development of three‐dimensionally printed implants for biomaterial‐based tissue engineering applications is currently an active research field. In order to meet the requirements of several applications, new biocompatible and bioresorbable polymer‐based materials are needed to design tailor‐made polymer/composite scaffolds. In the last decade, bioresorbable segmented poly(ester‐urethanes) (SPEU) have been extensively investigated for their applications in tissue engineering and many biomedical devices. In this work, 3D printed poly(ester‐urethane)/bioceramic composite scaffolds were successfully fabricated by fused deposition modeling for the first time. A twin‐screw extruder was used for making the SPEU composite filaments containing 5% and 10% wt/wt of glass‐ceramic particles. Both filaments and scaffolds were physically and chemically studied in terms of morphology, thermal properties, wettability, and mechanical properties. The resulting composite scaffolds could be remarkably interesting for potential applications in soft tissue engineering. Abstract :